In the Cultural Mirror: Influence of cultural factors on adoption of sanitation practices in rural areas: A case of Nzaui Sub-County, Makueni County, Kenya. (African Journal of Science, Technology and Social Sciences, 2022)
Provision of adequate sanitation is among the common approaches of preventing sanitation-related diseases. However, provision of sanitation facilities may not be a sustainable sanitation solution unless the population’s behavior changes and a positive perception is embraced. This paper underlines the influence of cultural factors on adoption of sanitation practices in rural areas. The article is based on field research employing convergent mixed methods research designs where both qualitative and quantitative data was gathered simultaneously. Quantitative data was gathered using structured questionnaires from 100 household heads selected using stratified and proportionate simple random sampling techniques. Qualitative data was collected using interview guides from a purposively selected focus group consisting of 9 participants. Quantitative data was analyzed using the Statistical Package for Social Sciences (SPSS) version 25 which generated descriptive and inferential statistics to unveil the relationship between variables. Qualitative data was organized into themes and presented in narratives. From the findings, a unit increase in gender roles would lead to a 0.147 increase in adoption of sanitation practices (p-value=0.000) and a unit increase in traditions would lead to a 0.032 decrease in adoption of sanitation practices (p-value=0.014). From the qualitative findings, some religions associated diarrhea with demons other than poor sanitation which was seen to facilitate adoption of poor sanitation practices. Further, the qualitative findings revealed that faeces left in the open could be used for witchcraft purposes, a tradition which had a positive impact on eradicating open defecation. The study recommends women inclusion in household sanitation matters. The study revealed the need for incorporation of leaders as advocates of sanitation behaviour change. The study also recommends future studies to examine adoption of sanitation practices alongside environmental, demographic and economic factors.
Keywords: Social factors; sanitation practices; rural; improved sanitation